Primary agricultural cooperatives in Malawi: Structure, conduct, and performance - Davis, Kristin E.; Kazembe, Cynthia; Benson, Todd; De Weerdt, Joachim; Duchoslav, Jan (International Food Policy Research Institute, 2023)
Primary agricultural cooperatives in Malawi, in contrast to other farmer-level organizations, have legal status and can own assets, borrow money for their operations, and sign contracts, making it easier for them to do business for the profit of their members. Conceptually, such cooperatives enable their member-farmers to achieve economies of scale for their commercial activities. By joining together in a cooperative, members can obtain commercial inputs at lower prices closer to wholesale prices than if they purchased the inputs as individuals. In selling their output, by aggregating their crops and other products into larger lots that the cooperative then negotiates to sell on their behalf, buyers can achieve greater efficiency in buying from them and can be expected to offer a premium over the prices that they would offer farmers selling those products individually. Cooperatives can also serve farmers in providing an important channel for obtaining information and advice to increase their productivity and the profitability of their farming. Moreover, by joining together to achieve common objectives in primary agricultural cooperatives, member-farmers can exercise greater influence on local and national policy issues of concern to them, while also building social cohesion, solidarity, and trust within their communities.